A creep–rupture model of synthetic fiber ropes for deepwater moorings based on thermodynamics. (August 2015) - Lian, Yushun; Liu, Haixiao; Huang, Wei; Li, Linan
Highlights: A creep–rupture model is developed to describe the viscoelastic property and damage evolution. Methods for identifying model parameters are proposed which apply to any component of ropes. Specially designed creep–rupture tests of HMPE strands at different loading levels are performed. The model is examined by creep tests of aramid yarns and HMPE strands. Abstract: The synthetic fiber ropes such as polyester, aramid and high modulus polyethylene (HMPE) are increasing applied to deepwater mooring systems for oil and gas exploitation. Due to that mooring ropes generally bear tensions for a long period, synthetic fiber ropes that are composed of the viscoelastic material would present creep behaviors and even the creep rupture, which is the failure mode of greatest concern especially for HMPE ropes and on which still less study can be found. A creep damage analysis of synthetic fiber ropes is of necessity to ensure the safe and economic operation of mooring systems. Therefore further investigation on the creep–rupture behavior is beneficial to fully establishing confidence in the viability of synthetic fiber ropes for deepwater moorings. In the present study, a creep–rupture model is proposed within the framework of thermodynamics to investigate the creep and damage behaviors of synthetic fiber ropes. Methods for identifying the model parameters are also proposed in detail, which apply to any component of fiber ropes such as the fiber, yarn, strand and rope. Experimental data of aramid yarns available from the literature are utilized to validate the constitutive model. Creep and creep–rupture tests of HMPE strands at different loading levels are specially performed to further examine the present model. The present work demonstrates that the proposed model can effectively describe the viscoelastic property and damage evolution of synthetic fiber ropes at different loading levels.